Flexural Strength Performance and Buckling Mode Prediction of Cold-formed Steel (C Section). (2015) - Susila, Adi; Tan, Jimmy
Abstract: One of the most common cold-formed steel shape is C section which can be used for roofing, framing partition and many more. To provide reliable and efficient cold-formed steel structures, the performance of the C section can be predicted by using bending test. Experimental and numerical work have been highlighted to investigate the effectiveness of strengthening method on the web section. Bending test has been used to determine flexural strength and buckling capacity which can be calculated by using either Effective Width Method (EWM) or Direct Strength Method (DSM). Both design methods were being specified in the Australian/New Zealand Standards for Cold-Formed Steel Structures AS/NZS 4600:2005 (Standards Australia 2005) or the North American Specification for Cold-Formed Steel Structural Members (AISI 2007) which can be applied as stiffeners within the intermediate web section. Based on the experimental developed at the Curtin University Sarawak Malaysia, a numerical simulation by using Abaqus has been employed to provide prediction of the behaviour of the C section under the four-point bending test (validation to the experimental result). The numerical analysis of the completed testing indicates that the stiffening provided on the intermediate web sections are not significantly increases the flexural strength capacity, however performance of buckling mode provided was slightly better.